Newborn screening for SMA in Southern Belgium - Boemer, F; Caberg, J-H; Dideberg, V; Dardenne, D; Bours, V; Hiligsmann, M; Dangouloff, T; Servais, L (Elsevier, 2019)
Approval was recently granted for a new treatment for spinal muscular atrophy (SMA). Given that the treatment is effective when administered early and the societal burden of SMA-related disability, the implementation of a newborn screening program is warranted. We describe the stepwise process that led us to launch a newborn screening program for SMA in Southern Belgium. Different political, ethical, and clinical partners were informed about this project and were involved in its governance, as were genetic and screening labs. We developed and validated a newborn screening method to specifically recognize homozygous deletions of exon 7 in the SMN1 gene. Subsequently, a 3-year pilot study has been recently initiated in one Belgian neonatal screening laboratory to cover 17.000 neonates per year. Coverage extension to all of Southern Belgium to screen 55.000 babies each year is underway.